The History of the Founding of the DDI Mangkoso - Ashari Ashari (Pattingalloang : Jurnal Pemikiran Pendidikan dan Penelitian Kesejarahan, 2026)
The Darud Da'wah Wal Irsyad (DDI) Islamic Boarding School in Mangkoso, formerly known as the MAI Mangkoso Islamic Boarding School, is an educational institution that has made a significant contribution to the struggle for independence and the development of the Indonesian people.  This pesantren, established in the early 20th century, has nurtured generations of Islamic scholars over several decades. This study is a literature review; the method used in this research is a qualitative approach with a descriptive methodology. The research findings indicate that the DDI Mangkoso Islamic Boarding School was established during the Dutch colonial era and experienced fluctuations in its development as a result of the dynamics of colonial rule.  This study of the boarding school’s development traces several historical periods: the Dutch colonial phase, the Japanese occupation, the early years of independence, the KNIL/NICA phase, and the post-KNIL/NICA eraKeywords: Dynamics, Islamic boarding school, Mangkoso